A novel inserted membrane technique for studies of mycorrhizal extraradical mycelium - Baláz, M; Vosátka, M (Mycorrhiza, 2001)
A simple "inserted membrane technique" (IMT) for sampling mycorrhizal extraradical mycelium (ERM) was developed as an alternative to the commonly used membrane filtration technique (MFT). The ERM of two types of mycorrhiza, orchid and arbuscular, was extracted by insertion of cellulose nitrate or cellulose acetate membrane filters (0.45-0.6 µm pore size) into the mycorrhizosphere of host plants. The membranes with adhered ERM were removed at harvest and stained with trypan blue for estimation of total hyphal length and with enzyme stains to indicate the viability of the ERM. There are two apparent advantages of the IMT over the MFT: (1) Samples were cleaner and easier to observe, particularly when the hyphae were stained for enzyme activities and (2) the ERM remained intact and, thus, was also suitable for observation of ERM morphology. There were statistically significant correlations between the lengths of ERM extracted from clinoptinolite using MFT and IMT for both mycorrhizal types tested, orchid mycorrhiza (r=0.63) and arbuscular mycorrhiza (r=0.80). Linear regression analysis indicated the best fit for the data obtained (P<0.05, n=14 for orchid mycorrhiza and P<0.001, n=26 for arbuscular mycorrhiza). Advantages of the new technique over other techniques for studying ERM are discussed.